2014
DOI: 10.3109/01443615.2014.896885
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome abnormality incidence in fetuses with cerebral ventriculomegaly

Abstract: Ventriculomegaly (VM) is a marker of aneuploidy and warrants a detailed examination of fetal anatomy. Chromosomal abnormalities worsen the fetal and neonatal prognosis significantly and karyotyping of fetuses is critically important when accompanying anomalies are detected. Here, we report the genetic results of 140 fetuses with isolated and non-isolated VM detected during a second trimester ultrasound examination followed by invasive in utero diagnostic procedures for karyotyping. VM was diagnosed in seven (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
4
20
1
Order By: Relevance
“…In infants with ventricular dilatation, severe ventriculomegaly associated with other malformations has a higher incidence of abnormal genetic testing than ventriculomegaly without malformations. In the literature, estimated abnormal genetic testing for ventriculomegaly without malformations is less than 10% . Similarly in our cohort, only five patients had chromosomal or clinically identified syndromes, with only one child with VATER and RES.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In infants with ventricular dilatation, severe ventriculomegaly associated with other malformations has a higher incidence of abnormal genetic testing than ventriculomegaly without malformations. In the literature, estimated abnormal genetic testing for ventriculomegaly without malformations is less than 10% . Similarly in our cohort, only five patients had chromosomal or clinically identified syndromes, with only one child with VATER and RES.…”
Section: Discussionsupporting
confidence: 52%
“…In the literature, estimated abnormal genetic testing for ventriculomegaly without malformations is less than 10%. [18][19][20] Similarly in our cohort, only five patients had chromosomal or clinically identified syndromes, with only one child with VATER and RES. Although more than two thirds of our cohort had genetic testing, we believe that the relatively lower incidence of genetic syndromes in our cohort may reflect our decision to exclude patients with central nervous system malformations such as encephaloceles and cystic posterior fossa malformations, particularly those with congenital muscular dystrophies.…”
Section: Discussionmentioning
confidence: 67%
“…Ventriculomegaly is diagnosed in utero (via ultrasonography) when the atrial diameter of one or both fetal lateral ventricles of the brain are measured as >10mm after 15 weeks' gestation. 3 Because of this known association, karyotyping of the fetus is indicated whenever fetal ventriculomegaly is detected. Studies have reported the prevalence of fetal ventriculomegaly to vary from 1 to 22 per 1000 pregnancies, and ventriculomegaly is strongly associated with an increased risk of a chromosomal anomaly.…”
mentioning
confidence: 99%
“…We believe that our result could be used for prenatal consulting to recommend chromosome analysis in a fetus with isolated VM. The common chromosomal abnormalities associated with VM are trisomies 13, 18, and 21 (Gezer et al, 2014;Sethna, Tennant, Rankin, & C. Robson, 2011), and those with advanced maternal age are trisomy 21, trisomy 18, XXX, and XXY (Halliday, Watson, Lumley, Danks, & Sheffield, 1995;Hook, Cross, Jackson, Pergament, & Brambati, 1988). We did not observe cases of trisomy 13 and 18, potentially due to the association with trisomy 13 and 18 to multiple malformations, which were excluded in our study.…”
Section: Discussionmentioning
confidence: 99%